A statistical approach to study anatomical changes of pink guava cultivar (Psidium guajava L. cv Arka Kiran) during its ripening at the room temperature storage (Kuwait Journal of Science)
The ripening of climacteric fruit like guava is a complex process that is highly coordinated with its cellular backbone. In the present study, we combined microscopy, spectrophotometry, and statistical analysis to evaluate the anatomical changes in the pink variety of guava during five ripening stages (pre-ripe, ripe, color-turn, half over-ripe, and over-ripe) during its storage at room temperature (28±2 °C). The cholorophyll content of the peel, as determined by the measurement of chlorophyll a, b, and total chlorophyll, showed a significant decrease during the maturation process (4.05, 4.53, and 8.62 μg/cm2, respectively, in the pre-ripe stage to ‘not detectable’ in the over-ripe stage). Gradual loss of integrity of the fruit pulp (pericarp) from the preserved bee-hive structure to cell mass was also monitored by studying the cellular anatomy with brightfield and scanning electron microscopy. The epidermal thickness and width of the cortical parenchyma cells revealed statistical differences from the initial pre-ripe stage to the final full-ripe stage. Finally, based on the cellular dimensions, multivariate analysis using PCA (Principal Component Analysis) tool grouped the stages into three clusters, namely, pre-ripe: ripe, color-turn: half-over ripe, and over-ripe stages. In conclusion, this study provided significant insights into cultivar-specific anatomical changes in guava fruit, with potential for future research to develop variants with longer post-harvest storage life. © 2024 The Author(s)